Can geocaching be an indicator of cultural ecosystem services? The case of the montado savannah-like landscape - do Rosario, Ines T.; Rebelo, Rui; Cardoso, Paulo; Segurado, Pedro; Mendes, Ricardo N.; Santos-Reis, Margarida (Ecological Indicators, 2019)
Cultural Ecosystem Services (CES) are difficult to assess and are seldom considered by land managers. Geocaching, an outdoor game that uses Global Positioning System (GPS) enabled devices to find hidden containers (geocaches) in certain locations, has been seldom used as a data source to assess CES. However, contrary to other crowdsourcing databases, geocaching allows to associate particular experiences to accurate locations. Furthermore, databases generated by geocachers provide an ideal case to compare revealed preferences (the frequency of visits to a specific geocache) with stated preferences (a posteriori evaluation of each location). We tested the relevance of geocaching databases as CES indicators using a dataset of 50 818 geocaches spread across continental Portugal, over eight land-use classes, with a focus on the montado (a high nature value farmland found in Southwestern Iberian Peninsula). We found that site visitation frequency was related with its availability, showing no revealed preference towards any land use. However, site evaluations by geocachers, measured either through the number of words describing the experience, the number of photos taken, or the number of votes for “favourite geocaches”, showed marked differences in their stated preferences, with higher appreciation for open land uses in general, and montado in particular, especially when compared to other forested landscapes. Our results may contribute to the design of regional development and land-use management policies of this threatened landscape, since they show the system’s strong potential as CES provider and, consequently, promoter of diversification of activities.
Keywords: Crowdsourcing databases; iberian peninsula; land use; spatial analysis; Stated and revealed preferences

Post-fire recolonisation of a montado area by the endangered Cabrera vole (Microtus cabrerae) - do Rosario, Ines T.; Mathias, Maria Da Luz (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2007)
The Cabrera vole is an endangered species frequently found in the montado, a savannah-like ecosystem well adapted to fire. Although it is assumed that regular burning is not very prejudicial to this vole, the impact of fire is unknown. This research studied, for the first time, recolonisation by the Cabrera vole after wildfire. Colonies were monitored over one year after a wildfire and the most relevant ecological features in their reestablishment were identified. During the first eight months, all the 18 surveyed colonies remained unoccupied. However, after one year, 11 were recolonised. Vegetation structure and composition in the colonies ( vegetation height, plant families diversity, percentage of bare ground and cover of shrubs before the fire), which are important features in offering protection and nutrition, were closely related to reoccupation of the colonies. Surprisingly, fire intensity did not influence recolonisation. Distance from unburned areas proved to be a factor that delayed recolonisation. The importance of the montado for this species was reinforced by the evidence that recolonisation occurred preferentially in colonies surrounded by this habitat type.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: CAP procedure; distance to unburned areas; MDS; Mediterranean; Portugal; Wildfire